SOLAR: GERAKAN SADAR OLAH LIMBAH PANGAN RUMAH TANGGA DENGAN PEMBERDAYAAN MASYARAKAT DESA KEMIRI - Zahrotul Farhani , Umi; Sefiyanti , Renita; Febianto, Prima; Ajeng Ulanuari , Riris; Putri, Alifiah; Wahyuni, Sri (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2024)
Kemiri Village is one of the villages located in Panti District, Jember Regency, with an area of 303 hectares and a population of 9,153 people (BPS Jember, 2022). The relatively dense population of Kemiri Village produces a large amount of household waste, both inorganic and organic. The waste problem in Kemiri Village has become serious due to the lack of awareness and skills of the community in managing household waste. Therefore, we have initiated a community service program "Solar: The Movement for Household Food Waste Management to Achieve Zero Waste by Empowering the Community of Kemiri Village" as a solution to the problems faced by our partners. The program implementation method consists of three stages: pre-program, implementation, and post-program. The implementation of the program involves socialization, training on the production of eco-enzyme and maggot cultivation, which is attended by members of the PKK and Karang Taruna. Through this program, it is hoped that the community will become aware of the importance of managing household waste, processing household food waste, and achieving zero waste.